The role of theory to develop and evaluate a toolkit to increase clinical measurement and interpretation of walking speed and distance in adults post-stroke - Salbach, Nancy M.; MacKay-Lyons, Marilyn; Solomon, Patricia; Howe, Jo-Anne; McDonald, Alison; Bayley, Mark T.; Veitch, Surabhi; Sivarajah, Lavan; Cacoilo, Joseph; Mihailidis, Alex (Disability and rehabilitation, 2022)
The iWalk study showed that 10-meter walk test (10mWT) and 6-minute walk test (6MWT) administration post-stroke increased among physical therapists (PTs) following introduction of a toolkit comprising an educational guide, mobile app, and video. We describe the use of theory guiding toolkit development and a process evaluation. We used the knowledge-to-action framework to identify research steps; and a guideline implementability framework, self-efficacy theory, and the transtheoretical model to design and evaluate the toolkit and implementation process (three learning sessions). In a before-and-after study, 37 of the 49 participating PTs completed online questionnaires to evaluate engagement with learning sessions, and rate self-efficacy to perform recommended practices pre- and post-intervention. Thirty-three PTs and 7 professional leaders participated in post-intervention focus groups and interviews, respectively. All sites conducted learning sessions; attendance was 50-78%. Self-efficacy ratings for recommended practices increased and were significant for the 10mWT (p ≤ 0.004). Qualitative findings highlighted that theory-based toolkit features and implementation strategies likely facilitated engagement with toolkit components, contributing to observed improvements in PTs' knowledge, attitudes, skill, self-efficacy, and clinical practice. The approach may help to inform toolkit development to advance other rehabilitation practices of similar complexity. Implications for Rehabilitation Toolkits are an emerging knowledge translation intervention used to support widespread implementation of clinical practice guideline recommendations. Although experts recommend using theory to inform the development of knowledge translation interventions, there is little guidance on a suitable approach. This study describes an approach to using theories, models and frameworks to design a toolkit and implementation strategy, and a process evaluation of toolkit implementation. Theory-based features of the toolkit and implementation strategy may have facilitated toolkit implementation and practice change to increase clinical measurement and interpretation of walking speed and distance in adults post-stroke.